Health assessment for urban rivers based on the pressure, state and response framework—A case study of the Shiwuli River. (April 2019) - Zhao, Y.W.; Zhou, L.Q.; Dong, B.Q.; Dai, C.
Highlights: Constructed an urban river health assessment system based on PSR framework. The system covers 23 multi-scale indexes of river basin and river corridor. Used the analytic hierarchy process and set pair analysis as assessment methods. The health assessment identified major problems of Shiwuli River accurately. Abstract: The health status of urban rivers is influenced by human activities and integrated management strategies. The current research on urban river health assessments insufficiently reflects river basin scale information, which leads to the incomplete identification of river health problems, and it is difficult to provide system support for urban river protection. We take the Shiwuli River in Hefei City as the research site, taking into account both the basin and the river itself, and consider the dual functions of river ecological services and social services. This research uses a combination of the subjective weighting method and the analytic hierarchy process to determine the weight of the indexes and a method based on set pair analysis to determine the health level. Moreover, we construct an assessment index system of urban river health, including the indexes of stress, state and response three sub-modules. The results indicate that the present status of the Shiwuli River is morbid, and it is facing many health problems, such as the intensive development of the river basin, a heavy pollution load, a serious lack of ecological flow, serious river pollution, weak pollution control strategies and poor ecological restoration. The multi-scale indexes covering the river basin and river corridors make the assessment index system based on the PSR (Pressure, State and Response) framework more systematic and scientific, which can more fully reflect the ecological status of rivers and more accurately identify their health problems.